2019
DOI: 10.1507/endocrj.ej19-0071
|View full text |Cite
|
Sign up to set email alerts
|

Random urinary gonadotropins as a useful initial test for girls with central precocious puberty

Abstract: Recent evidence indicates that urinary gonadotropins may be an alternative method for detecting pubertal disorders. The aim of this study was to evaluate the associations of first morning voided (FMV) and random urinary gonadotropins with the pubertal response to a gonadotropin-releasing hormone (GnRH) stimulation test to determine whether random urinary gonadotropins can be used as an alternative method for evaluating central precocious puberty (CPP). In total, 100 girls aged 6.0-8.9 years were enrolled. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Likewise, it was reported that a cutoff SD score of 2 for uLH had a sensitivity of 75% and a specificity of 92% in the COPENHAGEN puberty study with a large population ( 8 ). In another important study random urinary gonadotropins were recommended for the initial assessment of CPP in girls because there was no difference between FMV and random urinary gonadotropins levels ( 16 ). We consider that the main reason for various cutoff values was difference in sample size and hormone assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, it was reported that a cutoff SD score of 2 for uLH had a sensitivity of 75% and a specificity of 92% in the COPENHAGEN puberty study with a large population ( 8 ). In another important study random urinary gonadotropins were recommended for the initial assessment of CPP in girls because there was no difference between FMV and random urinary gonadotropins levels ( 16 ). We consider that the main reason for various cutoff values was difference in sample size and hormone assay.…”
Section: Discussionmentioning
confidence: 99%
“…The value and reference of uLH in well-suppressed patients should be confirmed in large-scale and multicenter studies. In addition, randomized urinary gonadotropins were promising in clinical practice ( 16 ), so further work is required to clarify whether elevated randomized uLH is sufficiently sensitive to replace FMV uLH.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity analysis illustrated that three studies in this meta-analysis might have caused bias, which referred to Shim et al’s [ 11 ], Yang et al’s [ 13 ] and Chen et al’s studies [ 14 ]. Subsequent sensitivity analyses were therefore conducted, and the results showed that the fourth record had the largest effect (Table 3 ).…”
Section: Resultsmentioning
confidence: 91%
“…The first included study not only evaluated the first-voided urinary gonadotropin levels but also tested random urinary gonadotropin levels; however, we only collected the first-voided urine results [ 11 ]. Only the value of ULH was examined in the second included study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation